Preface to the book This is life: the journey of uniportal VATS - Ng, Calvin Sze Hang (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
Uniportal video-assisted thoracic surgery (VATS), also known as single port VATS or single incision VATS has taken the world of minimally invasive thoracic surgery by storm. The technique originated more than a decade ago for minor procedures and stood still, until recent developments in surgical technique and instrumentation allowed the most complex of thoracic procedures to be performed by the uniportal approach. However, it is also the determination, courage, skill and unshakable belief of an individual, Dr Diego Gonzalez-Rivas that has shaped the uniportal world as we all know it today.